Wartime EU: consequences of the Russia – Ukraine war on the enlargement process. Issue 3 (3rd April 2023) - Anghel, Veronica; Džankić, Jelena
ABSTRACT: The European Union (EU) revived the enlargement process in response to the Russia-Ukraine war. That reaction compares to how the EU utilized this process following the wars in the Balkans in the 1990s. In this paper, we argue that on neither occasion was the inclusion of more states within EU borders a preferred EU working agenda. Instead, the EU used enlargement as a stabilization and security-building mechanism without guaranteeing membership as the end state. This observation has implications for the future of the enlargement process. We argue that the outcome of the previous rounds of enlargement was reactive and context-driven. Absent those same contextual factors, and although the EU reacts to the Russia-Ukraine war in a familiar sequence of incomplete decision-making, the outcome of this wartime enlargement negotiation process points in a different direction.